2021
DOI: 10.1088/1755-1315/653/1/012128
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of cookies from sorghum flour and almond flour with variations in the type of fat

Abstract: The substitution of wheat flour with almond flour and addition of vegetables fat can influence the final properties of cookies, enhance the taste, and eliminate skim milk use which produce lactose-free cookies. This study aims to determine the effect of different ratio of sorghum flour to almond flour and addition of various type of fat to the physical and chemical properties of cookies. This research used a factorial randomized block template (RBD) with study factors ratio of sorghum flour to almond flour (1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…These results are consistent with those of Nurani and Yuwono [ 36 ], who stated that the greater the amount of margarine added to taro cookies, the higher the water content. According to Sustriawan et al [ 20 ] the difference in water content between margarine and butter accounts for the water content of bread with the addition of 16% VCO.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are consistent with those of Nurani and Yuwono [ 36 ], who stated that the greater the amount of margarine added to taro cookies, the higher the water content. According to Sustriawan et al [ 20 ] the difference in water content between margarine and butter accounts for the water content of bread with the addition of 16% VCO.…”
Section: Resultsmentioning
confidence: 99%
“…The use of margarine, which is mineralised during the manufacturing process, prevents excessive heat. Sustriawan et al [ 20 ] showed that cookies made with margarine had higher ash content (0.67%) than cookies made using a mixture of margarine and VCO (0.40%) or cookies made with VCO alone (0.26%). This is also supported by the results of [ 37 ], who showed that biscuits made with margarine had a higher absorption rate of 1.46–1.62%, compared with biscuits made without margarine, which had a lower absorption rate of 1.23–1.41%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations